Impaired Antibody Response Following the Second Dose of the BNT162b2 Vaccine in Patients With Myeloproliferative Neoplasms Receiving Ruxolitinib - Ikeda, Daisuke; Terao, Toshiki; Miura, Daisuke; Narita, Kentaro; Fukumoto, Ami; Kuzume, Ayumi; Kamura, Yuya; Tabata, Rikako; Tsushima, Takafumi; Takeuchi, Masami; Hosoki, Takaaki; Matsue, Kosei (Frontiers in Medicine, 2022)
Data on the effect of ruxolitinib on antibody response to severe acute respiratory coronavirus 2 (SARS-CoV-2) vaccination in patients with myeloproliferative neoplasms (MPN) is lacking. We prospectively evaluated anti-spike-receptor binding domain antibody (anti-S Ab) levels after the second dose of the BNT162b2 (Pfizer-BioNTech) vaccine in MPN patients. A total of 74 patients with MPN and 81 healthy controls who were vaccinated were enrolled in the study. Of the MPN patients, 27% received ruxolitinib at the time of vaccination. Notably, MPN patients receiving ruxolitinib had a 30-fold lower median anti-S Ab level than those not receiving ruxolitinib (p < 0.001). Further, the anti-S Ab levels in MPN patients not receiving ruxolitinib were significantly lower than those in healthy controls (p < 0.001). Regarding a clinical protective titre that has been shown to correlate with preventing symptomatic infection, only 10% of the MPN patients receiving ruxolitinib had the protective value. Univariate analysis revealed that ruxolitinib, myelofibrosis, and longer time from diagnosis to vaccination had a significantly negative impact on achieving the protective value (p = 0.001, 0.021, and 0.019, respectively). In subgroup analysis, lower numbers of CD3+ and CD4+ lymphocytes were significantly correlated with a lower probability of obtaining the protective value (p = 0.011 and 0.001, respectively). In conclusion, our results highlight ruxolitinib-induced impaired vaccine response and the necessity of booster immunisation in MPN patients. Moreover, T-cell mediated immunity may have an important role in the SARS-CoV-2 vaccine response in patients with MPN, though further studies are warranted.